Development Of A Multi-lumen Diameter Common Carotid Artery Wall-less Phantom And Blood Mimicking Fluids For Doppler Ultrasound - Kyermang Kyense, Dakok (2021)
Flow phantoms with anatomically realistic geometry and high acoustic compatibility with real vessels are reliable tools in vascular ultrasound studies. A new common carotid artery (CCA) wall-less phantom with multi-lumen diameters has been presented to be used for ultrasound flow velocity studies using blood mimicking fluids (BMF) containing glucose and cholesterol. The phantom was constructed with 8 lumen diameters from 4.50 mm to 8.00 mm with a scanning depth of 7.5 mm, all within normal human carotid geometry. The tissue mimicking material (TMM) consists of konjac, carrageenan and gelatine as basic components mixed with other suitable components such as distilled water, aluminium oxide, potassium chloride, silicon carbide, glycerol and benzalkonium chloride. The BMF was prepared by mixing propylene glycol (PG), D(+)-glucose (DG) and poly (4-methystyrene) scatters in distilled water for the first BMF, followed by replacing the poly (4-methylstyrene) with cholesterol to form the second BMF. The constructed phantom was scanned using ultrasound machine to measure flow velocities, pulsatility index (PI) and resistivity index (RI) through the lumens and to test the effectiveness of the phantom. The phantom was found to have a speed of sound and attenuation of 1548.20±0.02 m/s and 0.35±0.02 dB/cm respectively at a frequency of 5 MHz. A very good BMF with glucose was produced having a density of 1.04±0.01 g/cm3, viscosity of 4.30±0.05 mpa.s, speed of sound of 1580.00±0.30 m/s and attenuation of 0.02±0.01 dB/cm at 5MHz